Effects of temperature and pressure on gas desorption in coal in an enclosed system: a theoretical and experimental study. (2016) - Feng, Zengchao; Zhao, Dong; Zhao, Yangsheng; Zhao, Jing; Liu, Zhixiang
The desorption of a gas from any type of coal depends on the gas's pressure and temperature. The adsorption capacity of coal decreases as temperature increase and gas pressure decrease. Desorption capacity increases as temperature rise, and then gas pressure of system also rises in a closed system. The objective of this paper was to determine the relationship between desorption temperature and gas pressure in a closed coal-gas system. At temperatures between 30°C and 240°C, three different types of coal samples (such as lean coal, anthracite and coke coal) were prepared for desorption experiments with methane and nitrogen. Curves describing the relationship between desorption pressure and temperature were obtained. Based on the Boltzmann energy distribution law and the ideal gas state equation, a theoretical model of the desorption pressure and temperature in the system considered was established. The Dubinin-Radushkevich equation was also introduced into the new model. Finally, the gas adsorption capacities of coal at any temperature and pressure could be forecast using the new mathematical model.